Social, Economic, and Cultural Obstacles to Creative Thinking among Social Researchers: A Sociological Study in Erbil City - Mohammed, Aso W. (Mitanni Journal of Humanitarian Sciences, 2022)
The importance of this research lies in the fact that, to the best of the current researcher’s knowledge, it is one of the rare studies, as the library suffers from a great lack of studies interested in this topic, and this topic was chosen because of the significant and influential role of social, economic, and cultural obstacles in reducing creative thinking, and where the current study aims to identify the social, economic, and cultural obstacles to creative thinking among social researchers in the city of Erbil, by applying to a sample of 150 social researchers in the Ministries of Justice and Social Affairs, depending on the analytical descriptive approach, and using the questionnaire tool. The results of the study showed that there is an average effect of each of the social and cultural obstacles on the development of creative thinking among social researchers, while the impact of economic obstacles was significant on the development of their creative thinking. The skill of maintaining direction, as well as, to a small degree, they have the ability to express ideas fluently, and formulate them in useful words that fit situation, while they have a very high degree of flexibility skill, as well as a large degree of problem sensitivity skill